Ensino de soluções químicas por meio da abordagem Ciência-Tecnologia-Sociedade (CTS) - Niezer, Tânia Mara (2012)
This study is the questioning about the possibilities of teaching in the classroom, the chemical content of solutions, related to the daily life of students, to provide the Scientific and Technological Literacy (ACT) by focusing Science-Technology-Society (CTS). The overall goal of this research is to develop and analyze the chemical content of education solutions relating to the daily lives of students by focusing CTS contributing to the Scientific and Technological Literacy (ACT). The study was conducted with 55 students from 2nd grade of high school, the course of an Agricultural Technician in State Center for Professional Education, the city of Rio Negro, Parana. The methodological approach was qualitative interpretative, with participant observation. Data collection occurred through photos and videos of activities, observation of activities performed by the students themselves, Pleas oral reports and notes in a field journal. The activities developed in this research were organized into fifteen (15) times in which it was sought to discuss and contextualize the social relations of science and technology through the study of chemical solutions, in an interdisciplinary way. The main results showed that the CTS approach in teaching Solutions, contributed to the appropriation of chemical concepts, students, and can transpose issues that involve day to day. During the classes students were more critical and reflective about the social implications in relation to science and technology issues. Another result obtained in this study consisted of developing a teaching guide that can be used as a methodological suggestion by teachers of high school chemistry.